Genetic determinants of fetal opiate exposure and risk of neonatal abstinence syndrome: Knowledge deficits and prospects for future research. Issue 3 (22nd July 2015) - Lewis, T; Dinh, J; Leeder, JS
<x xml:space="preserve">Abstract</x> Opiate‐dependent pregnant women receive opiate maintenance medications to prevent illicit use and withdrawal. Fetal opiate exposure causes central nervous system (CNS) alterations which manifest as postnatal physical withdrawal. The extensive variability in the Neonatal Abstinence Syndrome phenotype remains unexplained and may be related to variability in fetal exposure and response. Improved understanding of functionally significant genetic variants in pathways influencing placental opiate transfer and fetal response can lead to personalized maternal therapy and optimized neonatal outcomes.